Bolivia : 2009 Article IV Consultation; Staff Report; Staff Supplement; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report, 2010)
The staff report for Bolivia's 2009 Article IV Consultation describes economic developments and policies. The impact of the global recession on Bolivia has been milder than in other countries in the region. Lower commodity exports and remittances have resulted in a sharp narrowing of the external current account surplus. The financial system has been barely affected by the global crisis owing to its limited integration with international capital markets. As the economy gathers momentum, a tighter monetary policy is needed to reduce the risks of excessive credit creation, foreign-exchange pressures, and a pick-up in inflation.